2021
DOI: 10.1016/s2589-7500(21)00003-0
|View full text |Cite
|
Sign up to set email alerts
|

Face masks help control transmission of COVID-19

Abstract: success of the intervention. Rader and colleagues show a relationship between transmission and reported mask usage but did not see a step change in transmission when statewide mask mandates were introduced. 1 This finding suggests that, in the US, there is a disconnect between rules, messaging, and actions, and that further sociobehavioural research is needed on what motivates people who choose not to wear a mask to protect themselves and those around them.We declare no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, such hopes are under current practice not realistic. After state‐wide mask mandates, self‐reported mask wearing did not increase significantly in the US, indicating a disconnect between rules, messaging and actions, and that socio‐behavioural research is needed to reinforce mask wearing (Clapham and Cook, 2021 ). A discrepancy between self‐reported and observed mask wearing was also observed in developing countries such as Bangladesh and Kenya (Abaluck et al ., 2021 ; Jakubowski et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, such hopes are under current practice not realistic. After state‐wide mask mandates, self‐reported mask wearing did not increase significantly in the US, indicating a disconnect between rules, messaging and actions, and that socio‐behavioural research is needed to reinforce mask wearing (Clapham and Cook, 2021 ). A discrepancy between self‐reported and observed mask wearing was also observed in developing countries such as Bangladesh and Kenya (Abaluck et al ., 2021 ; Jakubowski et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social contact in populated areas fosters greater chances of contracting infectious diseases (Yang et al, 2017). Recent research on mask-wearing behavior during COVID-19 has found population density as a positive correlate of virus transmission (Rader et al, 2020) and that faces masks help control transmissions (Clapham and Cook, 2021) with experts calling for mask wearing in population-dense areas (Zhai, 2020). Therefore, we assumed that areas with greater population densities may be more at risk, and people within those regions are more likely to wear masks (Haischer et al, 2020).…”
Section: Population Densitymentioning
confidence: 99%
“…The results in this study, reinforce the evidence that in general, wearing masks can be beneficial to the community and that this beneficial effect is derived from the ability of masks to block the exhalation and inhalation of infectious viruses, regardless of the type of mask used, as shown in a review by Brooks and Butler (2021) [24] Data from different studies conducted in several countries have shown that the use of masks together with social distancing can reduce the transmission of SARS-CoV-2 and the number of cases of SARS-CoV-2 infection [11,[25][26][27][28]. A study performed by Ma et al (2020), which used an automated system that mimicked human breathing, showed that the virus-blocking rates of surgical and homemade masks were approximately 97% and 95%, respectively [29].…”
Section: Discussionmentioning
confidence: 99%